2008
DOI: 10.1029/2008gl034574
|View full text |Cite
|
Sign up to set email alerts
|

Aerial infrared imaging reveals large nutrient‐rich groundwater inputs to the ocean

Abstract: [1] Regional high-resolution (0.1°C, 0.5 m) low-altitude thermal infrared imagery (TIR) reveals the exact input locations and fine-scale mixing structure of massive, cool groundwaters that discharge into the coastal zone as both diffuse flows and as >30 large point-sourced nutrient-rich plumes along the dry western half of the large volcanic island of Hawaii. These inputs are the sole source of new nutrient delivery to coastal waters in this oligotrophic setting. Water column profiling and nutrient sampling sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
175
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(192 citation statements)
references
References 21 publications
(24 reference statements)
14
175
1
Order By: Relevance
“…SGD fluxes from the Hawaiian Islands are poorly quantified, having been modeled in a few discrete locations only (Johnson et al, 2008;Knee et al, 2008;Street et al, 2008;Peterson et al, 2009), but none of these efforts have targeted the total SGD flux from an entire island or the archipelago as a whole. The USGS has performed whole-island water budget studies for all the major Hawaiian Islands except for the island of Hawai'i, where the water budget has been described in several regional studies (performed by the USGS, the State of Hawai'i and private companies), which together cover the entire island.…”
Section: Hydrologymentioning
confidence: 99%
See 2 more Smart Citations
“…SGD fluxes from the Hawaiian Islands are poorly quantified, having been modeled in a few discrete locations only (Johnson et al, 2008;Knee et al, 2008;Street et al, 2008;Peterson et al, 2009), but none of these efforts have targeted the total SGD flux from an entire island or the archipelago as a whole. The USGS has performed whole-island water budget studies for all the major Hawaiian Islands except for the island of Hawai'i, where the water budget has been described in several regional studies (performed by the USGS, the State of Hawai'i and private companies), which together cover the entire island.…”
Section: Hydrologymentioning
confidence: 99%
“…For example, SGD from the island of Hawai'i has a temperature of ~19-21°C (Johnson et al, 2008;Peterson et al, 2009), andConrad et al (1997) showed that groundwater in deep drill holes on the east flank of Kilauea volcano is the same temperature from sea level down to ~500 m below sea level -~20-25°C. The results from Rad et al (2007) are therefore not directly comparable with our work.…”
Section: Water Chemistry and Chemical Fluxesmentioning
confidence: 99%
See 1 more Smart Citation
“…This value is insignificantly lower than our average value for Moloka'i of 52 ± 25 yr for AD 700-1800. However, the western Kona coast is known for large local groundwater discharge with 31 major point-source discharge plumes (surface area >13,000 m 2 ) along ~100 km of coastline (Johnson et al 2008). As the 14 C content in DIC of local groundwater may not be similar to that of surface ocean, the above coral ΔR value may be influenced by local groundwater discharge and is not used for the calculation of the weighted mean ΔR for Hawai'i, which is discussed later.…”
Section: Druffel Et Al (2001) Measured 14 C In Annually Banded Coralmentioning
confidence: 99%
“…[3] Despite comprehensive efforts, one gap in SGD science that has been challenging to fill is a lack of observations which link offshore information from isotopic or chemical tracer measurements [Cable et al, 1996a;Moore, 1996], seepage measurements [Michael et al, 2003;Moore et al, 2002], ground-based [Moore et al, 2002] and remote thermal measurements [Johnson et al, 2008] to subsurface environments in offshore areas, coasts and further inland. However, there have been some recent comprehensive studies [Martin et al, 2007;Breier et al, 2009].…”
Section: Introductionmentioning
confidence: 99%